The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1590/s0102-09352012000400015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis A virus in sea food in Iran

Abstract: The objective of this study was to determine the prevalence of Hepatitis A Virus (HAV) in sea food samples in the Isfahan and Shahrekord townships in Iran. From September 2010 to April 2011, a total of 300 samples of fresh fish, shrimp, crab and lobster were obtained from randomly selected retail stores in the Isfahan and Shahrekord townships in Iran. The samples were tested for the presence of HAV using a reverse transcriptase-polymerase chain reaction method. Out of the total number of samples examined, 8 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The total incidence of HAV amongst shellfish samples was 1.33%. Lower incidence rates of HAV in shellfish samples were reported in Italy (0.9%) (11) and South Korea (0.7%) (12), while higher incidence rates were observed in Iran (2.70%) (13) and Portugal (33%) (14). The total incidence of NoV GI amongst shellfish samples was 8.00%.…”
Section: Discussionmentioning
confidence: 92%
“…The total incidence of HAV amongst shellfish samples was 1.33%. Lower incidence rates of HAV in shellfish samples were reported in Italy (0.9%) (11) and South Korea (0.7%) (12), while higher incidence rates were observed in Iran (2.70%) (13) and Portugal (33%) (14). The total incidence of NoV GI amongst shellfish samples was 8.00%.…”
Section: Discussionmentioning
confidence: 92%
“…In accordance with these results, some studies have previously shown that S. aureus isolates may be negative for the coa gene. Momtaz et al reported that only 42 of 86 S. aureus isolates in milk samples from bovine mastitis cases contained the coa gene in PCR-RFLP analysis (17). In study of Karahan and Cetinkaya, the coa gene was detected in 80.5% of S. aureus strains isolated from subclinical cases of mastitis (14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they reported different coa-RFLP patterns among S. aureus isolates from goat, sheep and bovine milk samples(22). Momtaz et al reported the presence of certain coa genotypes of S. aureus in cases of mastitic in dairy herds in Isfahan, Iran(17).…”
mentioning
confidence: 99%